2021
DOI: 10.1097/md.0000000000025599
|View full text |Cite
|
Sign up to set email alerts
|

Drug-coated balloon angioplasty versus balloon angioplasty for treating patients with in-stent restenosis in the femoropopliteal artery

Abstract: Background: The introduction of endovascular surgery has led to frequent stent use, although in-stent restenosis (ISR) remains a challenging issue. Drug-coated balloon (DCB) and conventional balloon angioplasty (BA) are common endovascular procedures for addressing ISR in the femoropopliteal artery. However, there is controversy regarding which procedure provides the greatest benefit to patients. Methods: The PubMed, EMBASE, and Cochrane Central Register of Controlled T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Domestic studies have shown that, compared with conventional high-pressure balloons, cutting balloon angioplasty (CBA) can squeeze and cut plaques to a certain extent, reduce complications such as vascular dissection and loss, and can increase immediate lumen acquisition rate and minimum lumen area after stent implantation [ 8 ]. Previous studies have pointed out that because of its ability to provide anti-restenosis drugs to the vascular endothelium and the avoidance of multilayer stent implantation, the drug-coated balloon (DCB) has received different clinical indications including the treatment of ISR in the past few years [ 9 ]. Therefore, this study combined the two in the clinical treatment of DES-ISR, aiming to explore its clinical efficacy on DES-ISR, and to construct a prediction model for the occurrence of DES-ISR, so as to provide reference for the clinical prevention and treatment of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Domestic studies have shown that, compared with conventional high-pressure balloons, cutting balloon angioplasty (CBA) can squeeze and cut plaques to a certain extent, reduce complications such as vascular dissection and loss, and can increase immediate lumen acquisition rate and minimum lumen area after stent implantation [ 8 ]. Previous studies have pointed out that because of its ability to provide anti-restenosis drugs to the vascular endothelium and the avoidance of multilayer stent implantation, the drug-coated balloon (DCB) has received different clinical indications including the treatment of ISR in the past few years [ 9 ]. Therefore, this study combined the two in the clinical treatment of DES-ISR, aiming to explore its clinical efficacy on DES-ISR, and to construct a prediction model for the occurrence of DES-ISR, so as to provide reference for the clinical prevention and treatment of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…There is a focus on more complex and combined techniques for the treatment of ISRs which are producing more encouraging results such as DES, again with major limitations such as a stent length which excludes treating long stenosis. DCB shows superior results compared to traditional re-PTA with a stent and is becoming the technique of choice for ISRs [ 12 , 13 , 14 , 15 , 62 ]. Combined techniques such as laser atherectomy and DCB are also being developed and appear to be candidates to become the reference technique, but adequate studies are warranted [ 1 , 11 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another problem for which we are turning to combined procedures, as described above, is the degree of stenosis or calcification that does not allow for the passage of devices. For this reason, many stenoses or ISRs must be pretreated with traditional balloons to fragment the stenosing plaque, bringing the vessel back to an adequate caliber and allowing the absorption of drugs in situ [ 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD‐TLR and restenosis were also significantly less frequent with paclitaxel DCBs employing urea as the excipient such as the IN.PACT Admiral DCB. Similarly, a meta‐analysis of six trials with 541 patients with FP in‐stent restenosis demonstrated a relative risk of CD‐TLR of 0.38 [95% CI: 0.27–0.54] at 1 year 2 . The DCB groups had greater symptomatic improvement than PTA as well.…”
mentioning
confidence: 96%